The Relathionship Between CD31 Immunohistochemical Expression and Meningioma Grading Differences - Febriana, Nanggi Qoriatul; Rosyidi, Rohadi Muhammad; Januarman, Januarman; Rahim, Adelia Riezka; Prihatina, Lale Maulin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The proper management of meningioma patients requires a definitive diagnosis of the meningioma grade by examining the expression of CD31 in tumor blood vessels using immunohistochemical staining. This study aims to determine the relationship between CD31 immunohistochemical expression and the grading differences of meningiomas. Nine paraffin block samples from the surgical tissue of meningioma patients were used, with three samples each from grade I, grade II, and grade III meningiomas. Immunohistochemical staining for CD31 was then performed on each meningioma slide, and the samples were observed under a binocular light microscope with 200x magnification. The results showed CD31 expression in grade I as 90%, 40%, and 80%; in grade II as 80%, 80%, and 60%; and in grade III as 40%, 20%, and negative (0%). The statistical test results of this study indicate a strong negative correlation between CD31 immunohistochemical expression and meningioma grading differences. The higher the meningioma grade, the lower the CD31 expression found, and vice versa. This research is important to assist neurosurgeons in the proper management of meningioma patients, potentially preventing poor prognosis and complications. It is hoped that future studies will analyze the relationship between CD31 immunohistochemical expression with subtypes of each meningioma grade and their respective locations.